Efficient dressing of the wheel in ELID grinding by controllable voltage with force feed back - Saleh, Tanveer; Bishwas, Indraneel; Rahman, Mustafizur (Springer London, 2010)
Electrolytic in-process dressing (ELID) grinding is a new method for achieving ultraprecision surface on hard and brittle materials. In ELID grinding, pulsed direct current voltage is applied on the metal-bonded diamond wheels to ensure constant protrusion of sharp cutting grits throughout the grinding cycle. The peak dressing voltage is kept constant irrespective of the wheel sharpness in conventional ELID grinding, which may lead to overdressing of the grinding wheel. Grinding force ratio (which is also known as K value) is an indicator for the grit sharpness. In this paper, a new approach of wheel dressing has been proposed where the peak dressing voltage is varied according to the change in the K value during grinding. A Kistler three-component dynamometer has been used to monitor the grinding force ratio in real time for this purpose. The methodology to implement the new “dressing-on-demand” concept has been discussed thoroughly in this paper. The experimental comparison with the conventional ELID grinding has also been carried out to prove the advantages of the proposed system.